NSF (Nylon Synthetic Fiber) Effectiveness in Stabilizing Weak Subgrade Soil: An Experimental Investigation - Tarekegn Shumetie Demsie; Markos Tsegaye Beyene; Abuye Boja Lemma; Esayas Alemayehu (Advances in Civil Engineering)
Improvement in subgrade soil has always been an area of concern for highway and geotechnical engineers. Weak subgrade soil results in a greater thickness of the pavement layer, which increases the cost of pavement construction. It further leads to large deformations, which in turn cause continuous deterioration of the paved surface. To solve this problem, various engineering solutions and soil improvement mechanisms were previously proposed. This study was designed to investigate the stabilization of weak subgrade soil with nylon synthetic fiber (NSF) in a compromising combination. Previously, some investigations used a lower fiber content with a higher fiber length, whereas others used a lower fiber length with a higher fiber content. However, this investigation was uniquely designed to stabilize weak subgrade soil with the consideration of appropriate fiber length (10 mm and 20 mm) and content (0.5%, 1%, 1.5%, and 2.5%). The engineering properties of the soil, the effect of NSF on weak subgrade soil, various fiber content and aspect ratios, and the optimum content and critical fiber aspect ratio were investigated in a laboratory. The effect of fibers on compaction, CBR values, and CBR swell values has also been studied. Laboratory results on the modified compaction tests showed that maximum dry density (MDD) was increased with the increment of fiber content, whereas optimum moisture content (OMC) remained constant. The soaked CBR and CBR swell values of natural soil were 1.80% and 8.95%, respectively. Due to reinforcement, the percentage increase in soaked CBR value at the optimum NSF content is 265.3, 310.0, 282.8, and 342.2 for aspect ratios of 33.33, 66.67, 25, and 50, respectively, with reference to natural soil. Also, the percentage decrease in swelling is 34.7, 52.75, 43.55, and 36.9, respectively. Moreover, the CBR value increases with the increase in aspect ratio by keeping the diameter constant and decreases with the increase in aspect ratio by keeping the length constant. It was also observed that increasing the length and diameter of NSF further increased the CBR value of reinforced soil. This increment was substantial at a fiber content of 1.5% for an aspect ratio of 50 (length = 20 mm, diameter = 0.4 mm). There was also a decrease in the CBR swelling value with an increase in fiber content. Finally, this investigation concluded that the use of NSF is a solution to weak soils with regard to moisture and performance problems.